Duty to revolt : transnational and commemorative aspects of revolution - Souvlis, George; Karatzogianni, Athina (Digital activism and society., 2023)
Throughout the 19th century, revolutionary movements united intellectuals, artists, dissidents, and significant segments of the population in joint crusades in the name of justice or liberation against empires and aristocratic elites, often across class, religious, race and national lines. Duty to Revolt takes the Greek Revolution as a foundational historical departure point to investigate historical continuities and discontinuities in transnational and commemorative aspects of revolutionary wars. This edited collection provides an innovative and comprehensive contribution to the study of historical revolutions and their commemoration, as well as contemporary protests and uprisings, and how they are communicated today in everyday networked media. Duty to Revolt is the first work of its kind to take an interdisciplinary approach across historical time on this subject and bringing together leading and emerging scholars in several fields, merging history and political science with digital media and communication studies.